Manajemen Kinerja Pengajar Bahasa Arab di Mahad Saad Bin Abi Waqqash Palembang - Kms Badarudin; Maimunah Maimunah; Ainun Hofur (Studia Manageria, 2022)
. This study aims to describe and analyze lecturer performance management and the factors that influence it at Mahad Saad Bin Abi Waqqash Palembang during one semester of the teaching and learning process according to natural conditions. The type of research used by the author is field research with a qualitative model and a descriptive approach. The results of this study indicate that the performance of the Arabic language lecturer at Mahad Saad Bin Abi Waqqash Palembang has been categorized as good, which is reflected in the form of competence required, in order to carry out his profession in order to achieve satisfactory results including pedagogic competence, personality competence, professional competence, and social competence. The supporting factors for achieving the quality of lecturer performance are the motivation that arises from the vision and mission of Mahad Saad Bin Abi Waqqash Palembang, having a comfortable work environment, lecturers are the best alumni from Islamic universities from the Middle East, and facilities that support Arabic learning. Furthermore, the inhibiting factors are the welfare of lecturers who need attention, the lack of clarity or career paths for lecturers, and the lack of training programs for Mahad lecturers.